The influence of energy factors on the Balance of Payments of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
In my article I would like to discoes one of the main typical problem of a rapidly growing economy like Kazakhstan, deficit of electro energy and its effects on the Balance of payment country.
Keywords: deficit of electro energy